Is exercise/physical activity effective at reducing symptoms of post-traumatic stress disorder in adults — A systematic review - Jadhakhan, Ferozkhan; Lambert, Nichola; Middlebrook, Nicola; Evans, David W.; Falla, Deborah (Frontiers in Psychology, 2022)
Background: Exercise has been used to manage symptoms of post-traumatic stress disorder (PTSD). The effect of exercise on PTSD outcomes has been previously explored in several studies. However, it still remains unclear what type of exercise/physical activity, intensity and duration is most effective for reducing symptoms of PTSD. A systematic review was conducted to determine which forms of exercise or physical activity have the greatest effect on PTSD outcome scores including an evaluation of exercise frequency and volume. Methods: The following electronic databases were systematically searched from January 1980 to June 2021: MEDLINE, PsycINFO, PubMed and Web of Science. Inclusion criteria were studies investigating adults aged 18 or over, reporting the effect of exercise and physical activities on PTSD symptom outcome scores. Two reviewers independently extracted information on study characteristics, exposure and outcomes. 3217 articles were screened and 23 full text articles further assessed, with 13 RCT’s included in the review, covering seven exercise/physical activity interventions. The study protocol was registered prospectively with PROSPERO (CRD42021255131). Results: Thirteen studies from four countries involving a total of 531 patients were selected for inclusion. Individual forms of exercise/physical activity examined showed some effect on reducing PTSD symptoms but combined exercises (resistance training, aerobic, strength and yoga) administered over a 12 week period, three times a week for 30-60 minutes showed greater effects on PTSD symptoms. Conclusion: The limited evidence suggests that a combined exercise intervention has the best evidence for a having a beneficial effect on PTSD symptoms.